High-purity positive electrode lithium supplement material and preparation method and application thereof
Through the high-temperature sintering of Ni silencing and one-stage temperature-controlled sintering technology, high-purity Li2NiO2 lithium supplement material was prepared, which solved the problem of low purity caused by inappropriate lithium salt in lithium-ion batteries, and significantly improved the battery capacity and circulation performance.
Patent Information
- Application Number
- CN202411783878.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The lithium salts for preparing lithium supplement materials in existing lithium-ion batteries are not suitable, resulting in low purity of lithium supplements and affecting the battery capacity and circulation performance.
The lithium source is decomposed by high-temperature sintering of Ni sachet to produce high-purity Li2O, and mixed with the nickel source uniformly for sintering, controlling the oxygen content and temperature, and preparing high-purity Li2NiO2 lithium supplement material through one-stage temperature-controlled sintering.
It significantly improves the capacity and circulation performance of lithium-ion batteries, reduces the residual lithium and impurities content on the surface, and improves the purity and irreversible specific capacity of lithium supplement agents.
Smart Images

Figure CN119263360A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-purity positive electrode lithium supplement material and a preparation method and application thereof. Background Art
[0002] Emerging portable electronic devices and electric vehicles require high energy density lithium-ion batteries. Today, their energy density needs to be further improved to meet the growing demand for energy storage applications. In the past decade, nickel-rich layered oxide cathodes combined with graphite anodes have become a prominent battery system. The current nickel-rich ternary cathode has reached the basic limit of capacity, and the further improvement of the energy density of the whole battery is limited by the upper limit of graphite capacity. Among the various anode material alternatives, silicon-based materials have become the most promising choice for the next generation of battery systems. Although the anode capacity has increased with the introduction of silicon, the overall performance of the current silicon / NCM full battery is still unsatisfactory. Due to the serious side reactions that produce unstable solid electrolyte interface SEI, silicon-based anodes usually suffer significant capacity loss during the initial cycle, resulting in most of the lithium coming out of the cathode being consumed by irreversible reactions, which seriously reduces the energy density of the whole battery. To solve this problem, positive electrode lithium supplementation has become a very effective technical solution, which can reduce the initial lithium loss and improve the energy density of lithium-ion batteries by sacrificing specific lithium supplementation materials before cycling.
[0003] Li2NiO2, a positive electrode lithium supplement, is a commonly used lithium supplement material for lithium-ion batteries. In the public reports on the preparation of Li2NiO2, most of them only focus on the selection of nickel source, the mixing and sintering process of nickel source and lithium source, the selection of dopant, the selection of coating agent, etc., and there is very little research on the selection of lithium salt. As one of the main raw materials for the preparation of Li2NiO2, it plays a vital role in the purity, residual lithium and capacity of the product Li2NiO2, and thus affects the improvement effect of the battery system after mixing with lithium battery positive electrode materials. Chinese invention patent CN113571781B discloses a method for preparing lithium supplement Li2NiO2, which uses a composite lithium salt and a nickel source to mix, sinter and crush, and prepare a lithium supplement additive for the positive electrode of lithium-ion batteries. Among them, the lithium source uses a mixed composite lithium salt, and it is necessary to mix three different lithium salts and sinter them at high temperature in vacuum and crush them to obtain a certain proportion of composite lithium salt. The steps are cumbersome and the cost is high. The proportion of the obtained mixed lithium salt is not easy to control, which may lead to poor consistency of the final Li2NiO2. In addition, Chinese invention patent CN109786746A discloses a method for preparing lithium supplement Li2NiO2. The lithium salt Li2O used in this method is prepared by high-temperature calcination of Li2CO3 in an inert atmosphere. The purity of Li2O is greater than 99.9%. The subsequent solid-solid reaction with the nickel source is prone to incomplete reaction, resulting in a high residual lithium content in the product and low purity. Summary of the invention
[0004] The main technical problem solved by the present invention is to overcome the problems mentioned in the above background technology that the lithium salt used to prepare the lithium supplement agent is not suitable and the purity of the lithium supplement agent is not high, and provide a high-purity positive electrode lithium supplement agent material and its preparation method and application. The lithium supplement agent material has high purity and irreversible specific capacity, low surface residual lithium, and can significantly improve the capacity and cycle performance of the battery after being mixed with the lithium battery positive electrode material.
[0005] The present invention provides a method for preparing a high-purity positive electrode lithium supplement material, wherein the lithium supplement material has a general chemical formula of Li2NiO2, and the preparation method comprises the following steps:
[0006] (1) Decomposition of lithium source: Place the lithium source in a Ni sagger at room temperature, heat it at a certain heating rate in an atmosphere furnace under a nitrogen or argon protective atmosphere, keep it warm for a period of time, cool it down to room temperature naturally, and crush and grind it to obtain a product whose main component is Li2O;
[0007] (2) Mixed sintering: the product obtained in step (1) is uniformly mixed with lithium salt and nickel source, and sintered. In an atmosphere furnace, under a nitrogen or argon protective atmosphere, the temperature is increased at a certain heating rate, kept at the temperature for a period of time, cooled naturally to room temperature, and crushed and pulverized;
[0008] (3) Demagnetization: Demagnetize the material crushed in step (2), and obtain the high-purity positive electrode lithium supplement material after screening.
[0009] Furthermore, in step (1), the temperature is raised to 750-950°C at a heating rate of 1-5°C / min and kept at this temperature for 2-6 hours; in step (2), sintering is performed by a one-stage temperature-controlled sintering method; the temperature is raised to 600-780°C at a heating rate of 1-3°C / min and kept at this temperature for 5-15 hours.
[0010] Furthermore, the lithium source in step (1) is one or both of lithium hydroxide and lithium hydroxide monohydrate, the initial oxygen content in the atmosphere furnace is in the range of 200-1000 ppm, and the components of the product obtained in step (1) are, by mass, 95.0%<Li2O<99.0%, and 1.0%<NiO<3.5%.
[0011] Furthermore, the lithium salt in step (2) is one or both of lithium hydroxide and lithium hydroxide monohydrate; and the nickel salt is one or more of nickelous oxide, nickel trioxide or nickel hydroxide.
[0012] Furthermore, the mass ratio of Li2O in the product of step (1) used in step (2) to LiOH in the lithium salt used in the mixture is (8.8-9.5):1, and the molar ratio of the total Li in the two lithium salts to the total Ni in the mixture is (2.0-2.3):1, wherein the total Ni includes a small amount of NiO in step (1) and Ni in the nickel source added in step (2).
[0013] Furthermore, in step (2), the oxygen content of the atmosphere furnace is less than 10 ppm.
[0014] Furthermore, the mesh size of the sieve used for sieving in step (3) is 350-400 mesh, the average particle size D50 is 8.5-18.0 μm, and the magnetic material content after demagnetization is less than 50 ppb.
[0015] Furthermore, the purity of the lithium supplement material is >95%, the total amount of residual lithium is <3%, the average particle size D50 is 8.5-18.0 μm, and the specific surface area is 0.22-0.80 ㎡ / g.
[0016] The present invention provides a high-purity positive electrode lithium supplement material, which is prepared by the above method.
[0017] The present invention provides a lithium ion battery, wherein the positive electrode lithium supplement material mentioned above is used in the positive electrode material, and the battery has an initial charge specific capacity of >425 mAh / g and an irreversible specific capacity of 280-340 mAh / g.
[0018] The present invention also provides an application of a high-purity positive electrode lithium supplement material in a lithium ion battery. Beneficial Effects
[0019] (1) The present invention uses Ni sagger to sinter and decompose lithium source at high temperature to prepare Li2O. In addition to Li2O, the product also contains a small amount of NiO. When the lithium source undergoes a high-temperature melting decomposition reaction, a small amount of O2 exists in the atmosphere furnace, causing the Ni sagger to undergo a micro-reaction to generate a small amount of transition metal oxide NiO. The catalytic effect of the transition metal ions can significantly reduce the decomposition temperature of the lithium source, making the prepared Li2O particles uniform and small in size. When it is subsequently mixed with the nickel source to prepare the lithium supplement Li2NiO2, the mixing is more uniform, so that the reactant particles are fully in contact with each other, thereby generating a lithium supplement material Li2NiO2 with a higher purity.
[0020] (2) The small amount of NiO contained in the Li2O prepared by the present invention is used as one of the raw nickel sources for the subsequent reaction. Compared with the nickel source directly added, the small amount of NiO has a larger contact area with Li2O, which is conducive to the reaction, thereby increasing the nucleation reaction rate of the lithium supplement material Li2NiO2, significantly reducing the content of impurity NiO and surface residual lithium in the product, and improving the purity and irreversible specific capacity of the lithium supplement material Li2NiO2. Adding the lithium supplement material prepared by the present invention to the positive electrode active material of a lithium ion battery can significantly improve the capacity and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] FIG1 is an XRD diagram of a product obtained by high-temperature decomposition of a lithium source using a Ni sagger in Example 1 of the present invention;
[0022] FIG2 is an XRD diagram of the lithium supplement material prepared in Example 1 of the present invention;
[0023] FIG3 is a SEM image of the product obtained by high-temperature decomposition of a lithium source using a Ni sagger in Example 1 of the present invention;
[0024] FIG. 4 is a SEM image of the lithium supplement material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to the embodiments. Example 1
[0026] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace was 650ppm, the temperature was increased to 900℃ at a heating rate of 3℃ / min, kept warm for 5h, and naturally cooled to room temperature. The mass percentage of the main components of the product obtained after crushing and grinding was 97.2% Li2O and 2.5% NiO.
[0027] The prepared Li2O, LiOH and NiO are prepared according to the molar ratio of Li to Ni of 2.1:1, wherein Ni includes a small amount of NiO contained in Li2O and Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide is 9.0:1, and they are evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 660℃ at a heating rate of 2℃ / min, and the temperature is kept for 10h, and the temperature is naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Example 2
[0028] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace was 520ppm, the temperature was increased to 800℃ at a heating rate of 3℃ / min, kept warm for 5h, the furnace pressure was 5pa, and the temperature was naturally cooled to room temperature. The mass percentage of the main components of the product obtained after crushing and pulverization was 98.5% Li2O and 1.2% NiO.
[0029] The prepared Li2O, LiOH and NiO are prepared according to the molar ratio of Li to Ni of 2.1:1, wherein Ni includes a small amount of NiO contained in Li2O and Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide is 9.2:1, and they are evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 720℃ at a heating rate of 2℃ / min, and the temperature is kept for 10h, and the temperature is naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Example 3
[0030] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, with an initial oxygen content of 650ppm, and heated to 850℃ at a heating rate of 3℃ / min, kept warm for 5h, and naturally cooled to room temperature. The mass percentage of the main components of the product obtained after crushing and grinding was 97.8% Li2O and 1.9% NiO.
[0031] The prepared Li2O, LiOH and NiO are prepared according to the molar ratio of Li to Ni of 2.1:1, wherein Ni includes a small amount of NiO contained in Li2O and Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide is 9.0:1, and they are evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 660℃ at a heating rate of 2℃ / min, and the temperature is kept for 10h, and the temperature is naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Example 4
[0032] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, with an initial oxygen content of 520ppm, and heated to 880℃ at a heating rate of 3℃ / min, kept warm for 5h, and naturally cooled to room temperature. The mass percentage of the main components of the product obtained after crushing and grinding was 98.2% Li2O and 1.5% NiO.
[0033] The prepared Li2O, LiOH and NiO were prepared according to the molar ratio of Li to Ni of 2.05:1, wherein Ni includes a small amount of NiO in Li2O and Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide was 9.4:1, and they were evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace was 8ppm, and the temperature was increased to 750℃ at a heating rate of 2℃ / min, and kept warm for 10h, and naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Comparative Example 1
[0034] Li2O with a commercial purity greater than 99% is mixed with LiOH and NiO at a molar ratio of Li to Ni of 2.1:1, wherein the mass ratio of Li2O to lithium hydroxide is 9.0:1. The mixture is evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 660℃ at a heating rate of 2℃ / min, kept warm for 10h, naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Comparative Example 2
[0035] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, with an initial oxygen content of 650ppm, and heated to 720℃ at a heating rate of 3℃ / min, kept warm for 5h, and naturally cooled to room temperature. The mass percentages of the main components of the product obtained after crushing and grinding were 94.8% for Li2O, 2.0% for NiO, and 2.9% for LiOH.
[0036] The prepared Li2O, LiOH and NiO are prepared according to the molar ratio of Li to Ni of 2.1:1, wherein Ni includes a small amount of NiO contained in Li2O and Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide is 9.0:1, and they are evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 660℃ at a heating rate of 2℃ / min, and the temperature is kept for 10h, and the temperature is naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Comparative Example 3
[0037] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, with an initial oxygen content of 650ppm, and heated to 980℃ at a heating rate of 3℃ / min, kept warm for 5h, and naturally cooled to room temperature. The mass percentage of the main components of the product obtained after crushing and grinding was 94.4% Li2O and 5.5% NiO.
[0038] The prepared Li2O, LiOH and NiO are prepared according to the molar ratio of Li to Ni of 2.1:1, wherein Ni includes a small amount of NiO contained in Li2O and Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide is 9.0:1, and they are evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 660℃ at a heating rate of 2℃ / min, and the temperature is kept for 10h, and the temperature is naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Comparative Example 4
[0039] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, with an initial oxygen content of 10ppm, and heated to 900℃ at a heating rate of 3℃ / min, kept for 5h, and naturally cooled to room temperature. The mass percentage of the main component of the product obtained after crushing and grinding was 99.7% Li2O.
[0040] The prepared Li2O, LiOH and NiO were prepared according to the molar ratio of Li to Ni of 2.1:1, wherein Ni refers to the Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide was 9.0:1, and they were evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace was 8ppm, and the temperature was increased to 660℃ at a heating rate of 2℃ / min, and kept warm for 10h, and naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Comparative Example 5
[0041] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace was 8000ppm, the temperature was increased to 900℃ at a heating rate of 3℃ / min, kept warm for 5h, and naturally cooled to room temperature. The mass percentage of the main components of the product obtained after crushing and grinding was 94.5% Li2O and 5.2% NiO.
[0042] The prepared Li2O, LiOH and NiO are prepared according to the molar ratio of Li to Ni of 2.1:1, wherein Ni includes a small amount of NiO contained in Li2O and Ni in the added NiO. The mass ratio of Li2O to lithium hydroxide is 9.0:1, and they are evenly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 660℃ at a heating rate of 2℃ / min, and the temperature is kept for 10h, and the temperature is naturally cooled to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Comparative Example 6
[0043] At room temperature, lithium hydroxide monohydrate was placed in a Ni sagger, in an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace was 650ppm, the temperature was increased to 900℃ at a heating rate of 3℃ / min, kept warm for 5h, and naturally cooled to room temperature. The mass percentage of the main components of the product obtained after crushing and grinding was 97.2% Li2O and 2.5% NiO.
[0044] The prepared Li2O and NiO are prepared according to a molar ratio of Li to Ni of 2.1:1, wherein Ni includes a small amount of NiO contained in Li2O and Ni in the added NiO. They are uniformly mixed and sintered by a one-stage temperature-controlled sintering method. In an atmosphere furnace, under a nitrogen protective atmosphere, the initial oxygen content in the furnace is 8ppm, and the temperature is increased to 660℃ at a heating rate of 2℃ / min, kept warm for 10h, cooled naturally to room temperature, crushed, pulverized, demagnetized, and passed through a 400-mesh sieve to obtain the lithium battery positive electrode lithium supplement material Li2NiO2. Test Example 1
[0045] The positive electrode lithium replenisher material Li2NiO2 of Example 1 is selected as the lithium replenisher, and polycrystalline NCM811 is selected as the positive electrode active material. The amount of the lithium replenisher added is 3wt% of the positive electrode active material. The positive electrode active material and the lithium replenisher are used as a composite positive electrode active material. According to the mass ratio of composite active positive electrode material: conductive agent SP: binder PVDF = 97:1.5:1.5, a solution with a solid content of 70% is prepared, and the positive electrode slurry is evenly stirred to obtain a positive electrode slurry, which is coated on aluminum foil and assembled into a 604062 type soft pack battery. After the soft pack battery is prepared, conventional formation is performed, the formation voltage is 2.75-4.25V, and the charge and discharge rate is 1C. Test Example 2
[0046] The positive electrode lithium replenisher material Li2NiO2 of Comparative Example 1 was selected as the lithium replenisher, and polycrystalline NCM811 was selected as the positive electrode active material. The amount of the lithium replenisher added was 3wt% of the positive electrode active material. The positive electrode active material and the lithium replenisher were used as a composite positive electrode active material. The mass ratio of the composite active positive electrode material: conductive agent SP: binder PVDF = 97:1.5:1.5 was used to prepare a solution with a solid content of 70%. The solution was stirred evenly to obtain a positive electrode slurry, which was coated on an aluminum foil and assembled into a 604062 type soft-pack battery.
[0047] After the soft pack battery is prepared, conventional formation is performed, the formation voltage is 2.75-4.25V, and the charge and discharge rate is 1C. Evaluation of the physicochemical indicators and electrical properties of the positive electrode lithium supplement material prepared in the embodiment and comparative example.
[0048] The purity, residual lithium, capacity and specific surface area of the obtained positive electrode lithium supplement material were evaluated in the following manner.
[0049] (1) Purity
[0050] Place the powder sample in the sample slot and compact it, then put it into the sample rack of the XRD diffractometer and close the XRD diffractometer door. Set the scanning range to 15°-75° and the scanning speed to 15° / min, and start the test. The test results are quantitatively analyzed using XRD analysis software to calculate the relative mass fraction of the substances contained.
[0051] (2) Residual lithium
[0052] Preparation of sample solution: Place a 250mL dry beaker on an analytical balance, weigh 20g±0.0005g of lithium supplement material sample, record the mass as m, put a stirrer in the beaker, use a 100mL measuring cylinder to accurately measure 100mL of RO water with a water temperature of 25±2℃, slowly add it to the beaker, then seal the beaker mouth with plastic film and place it on a magnetic stirrer, stir at room temperature for 20 minutes, filter into a 50mL volumetric flask within 5 minutes after stirring, rinse the funnel and volumetric flask with the filtrate 2-3 times, and cool to room temperature. Use a clean pipette to suck and release the filtrate so that the concave surface of the filtrate is tangent to the scale line of the volumetric flask to obtain the sample solution.
[0053] Determination of residual lithium: Pour 50mL of the sample solution in the volumetric flask into a 250mL conical flask, rinse the volumetric flask three times with distilled water, and transfer the rinse solution to the conical flask. Add 1-2 drops of phenolphthalein indicator to the conical flask, select a hydrochloric acid standard solution of appropriate concentration, CHCL, and titrate the test solution until the red color disappears completely, reaching the endpoint of the first step of titration, and record the volume V1 of the hydrochloric acid standard solution consumed in the titration. Add 4-5 drops of methyl red indicator to the conical flask, and continue to titrate with the hydrochloric acid standard solution until the solution changes from yellow to bright red, which is the endpoint of the second step of titration, and record the volume V2 of the hydrochloric acid standard solution consumed in the titration at this time.
[0054] The content of Li2CO3 and LiOH is expressed as mass percentage and calculated as follows:
[0055]
[0056] Where: V1---the volume of hydrochloric acid standard solution consumed in the first step of titration, in mL;
[0057] V2---the total volume of hydrochloric acid standard solution consumed in the two-step titration, in mL; m---sample mass, in g; CHCL---molar concentration of hydrochloric acid standard solution, in mol / L.
[0058] (3) Capacity
[0059] The positive electrode lithium supplement material was assembled into a 2016-type button cell, and the slurry formula was lithium supplement: conductive agent SP: binder PVDF = 9:0.5:0.5: After production, it was formed at 23°C with 0.1C charge and discharge, 3-4.3V, and the cut-off current was 0.01C.
[0060] (4) Specific surface area
[0061] The BET surface area was measured using a nitrogen adsorption method.
[0062] Table 1 Comparative data of examples and comparative examples
[0063] Table 2 Comparative data of test cases evaluate
[0064] As can be seen from FIG. 1 , the lithium salt prepared by sintering the lithium source in a Ni sagger at high temperature in Example 1 mainly contains Li2O and a small amount of NiO.
[0065] It can be seen from Table 1 that compared with the positive electrode lithium replenisher material prepared in Example 1, the positive electrode lithium replenisher material prepared in Comparative Example 1 has lower purity and irreversible specific capacity, and higher residual lithium. This is because the Li2O prepared in Example 1 contains a small amount of NiO. This small amount of NiO has a large contact area with Li2O, which is conducive to the reaction, improves the nucleation reaction rate of the lithium replenisher material Li2NiO2, and can significantly reduce the content of impurity NiO in the product and the residual lithium on the surface, thereby improving the purity and irreversible specific capacity of the lithium replenisher Li2NiO2.
[0066] As can be seen from Table 1, compared with the positive electrode lithium supplement material prepared in Example 1, the purity and irreversible specific capacity of the positive electrode lithium supplement materials prepared in Comparative Examples 2 and 3 are lower, and the residual lithium is higher. This is because the temperature of the high-temperature sintering of the lithium source with Ni sagger in Comparative Example 2 is lower, the lithium source reaction is incomplete, and there is a small amount of unreacted LiOH, resulting in the prepared Li2O having low purity and low activity when mixed with the nickel source for sintering, which is not conducive to the generation of lithium supplement materials. In contrast, the temperature of the high-temperature sintering of the lithium source with Ni sagger in Comparative Example 3 is higher, and the Li2O generated by the reaction reacts excessively with the Ni sagger, resulting in low purity of Li2O, and low activity when mixed with the nickel source for sintering later, which is not conducive to the generation of lithium supplement materials. Therefore, the temperature of high-temperature decomposition of the lithium source with Ni sagger cannot be too low or too high, and it is more appropriate to control it in the range of 780-950°C to obtain Li2O with higher purity.
[0067] As can be seen from Table 1, compared with the positive electrode lithium supplement material prepared in Example 1, the purity and irreversible specific capacity of the positive electrode lithium supplement material prepared in Comparative Examples 4 and 5 are lower, and the residual lithium is higher. This is because when Li2O is prepared in Comparative Example 4, the initial oxygen content in the furnace is too low, and O2 is basically absent, resulting in the presence of no NiO in the decomposition product. When the lithium supplement material Li2NiO2 is prepared by uniformly mixing with the added nickel source and sintering at high temperature, the nucleation reaction rate is low, which is not conducive to the reaction. When Li2O is prepared in Comparative Example 5, the initial oxygen content in the furnace is too high, which prompts the lithium source to undergo an oxidation reaction with the Ni sagger, generating more NiO, resulting in the low purity of the prepared Li2O, and the low activity when mixed with the nickel source for subsequent sintering, which is not conducive to the generation of the lithium supplement. Therefore, the initial oxygen content in the furnace for high-temperature decomposition of the lithium source with the Ni sagger cannot be too low or too high, and it is more appropriate to control the range of 200-1000ppm to obtain Li2O with higher purity.
[0068] It can be seen from Table 1 that compared with the positive electrode lithium replenisher material prepared in Example 1, the positive electrode lithium replenisher material prepared in Comparative Example 6 has lower purity and irreversible specific capacity, and higher residual lithium. This is because no lithium hydroxide was added during mixing in Example 6, and the high-temperature sintering reaction was a pure solid-solid phase reaction, the material contact was insufficient, and the reaction was not complete. However, a small amount of high-temperature fusible lithium hydroxide was added during mixing in Example 1, which was conducive to sufficient contact and reaction of the materials, and the prepared lithium replenisher material had higher purity and lower residual lithium.
[0069] As can be seen from Table 2, the positive electrode lithium replenisher material Li2NiO2 prepared in Example 1 of the present invention has a significantly improved first charge specific capacity after being applied to soft-pack lithium-ion batteries, compared with the positive electrode lithium replenisher material in Comparative Example 1, while the first discharge specific capacity does not change much, the available irreversible specific capacity is large, the first efficiency loss rate caused by the lithium replenisher is large, and more lithium can be supplemented to the negative electrode, and the lithium replenishment effect is very good. The lithium loss of the positive electrode material will be significantly reduced, which is beneficial to the subsequent cycle performance.
Claims
1. A method for preparing a high-purity positive electrode lithium supplement material, wherein the lithium supplement material has a general chemical formula of Li2NiO2, characterized in that: The preparation method comprises the following steps: (1) Decomposition of lithium source: Place the lithium source in a Ni sagger at room temperature, heat it at a certain heating rate in an atmosphere furnace under a nitrogen or argon protective atmosphere, keep it warm for a period of time, cool it down to room temperature naturally, and crush and grind it to obtain a product whose main component is Li2O; (2) Mixed sintering: the product obtained in step (1) is uniformly mixed with lithium salt and nickel source, and sintered. In an atmosphere furnace, under a nitrogen or argon protective atmosphere, the temperature is increased at a certain heating rate, kept at the temperature for a period of time, cooled naturally to room temperature, and crushed and pulverized; (3) Demagnetization: Demagnetize the material crushed in step (2), and obtain the high-purity positive electrode lithium supplement material after screening.
2. The method for preparing a high-purity positive electrode lithium supplement material according to claim 1, characterized in that: In step (1), the temperature is raised to 750-950°C at a heating rate of 1-5°C / min and kept at this temperature for 2-6 hours. In step (2), the sintering is carried out by a one-stage temperature-controlled sintering method; the temperature is raised to 600-780°C at a heating rate of 1-3°C / min and kept at this temperature for 5-15 hours.
3. The method for preparing a high-purity positive electrode lithium supplement material according to claim 1, characterized in that: The lithium source in step (1) is one or both of lithium hydroxide and lithium hydroxide monohydrate, the initial oxygen content in the atmosphere furnace is in the range of 200-1000 ppm, and the components of the product obtained in step (1) are, by mass, 95.0%<Li2O<99.0%, and 1.0%<NiO<3.5%.
4. The method for preparing a high-purity positive electrode lithium supplement material according to claim 1, characterized in that: The lithium salt in step (2) is one or both of lithium hydroxide and lithium hydroxide monohydrate; the nickel salt is one or more of nickelous oxide, nickel trioxide or nickel hydroxide.
5. The method for preparing a high-purity positive electrode lithium supplement material according to claim 1, characterized in that: The mass ratio of Li2O in the product of step (1) used in step (2) to LiOH in the lithium salt used in the mixture is (8.8-9.5):
1. At the same time, the molar ratio of the total Li in the two lithium salts to the total Ni in the mixture is (2.0-2.3):1, wherein the total Ni includes a small amount of NiO in step (1) and Ni in the nickel source added in step (2).
6. The method for preparing a high-purity positive electrode lithium supplement material according to claim 1, characterized in that: In step (2), the oxygen content of the atmosphere furnace is less than 10 ppm.
7. The method for preparing a high-purity positive electrode lithium supplement material according to claim 1, characterized in that: The mesh number of the sieve used for sieving in step (3) is 350-400 mesh, the average particle size D50 is 8.5-18.0 μm, and the magnetic material content after demagnetization is <50 ppb; the purity of the lithium supplement material is >95%, the total amount of residual lithium is <3%, the average particle size D50 is 8.5-18.0 μm, and the specific surface area is 0.22-0.80 m2 / g.
8. A high-purity positive electrode lithium supplement material, characterized in that: The method is prepared by any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: The positive electrode lithium supplement material according to claim 8 is added to the positive electrode material, and the battery has an initial charge specific capacity of >425 mAh / g and an irreversible specific capacity of 280-340 mAh / g.
10. Use of the high-purity positive electrode lithium supplement material as claimed in claim 8 in lithium-ion batteries.
Citation Information
Patent Citations
Positive plate, lithium-ion battery positive lithium-supplementing material and preparation method of material
CN109786746A
Lithium supplement agent and preparation method and application thereof
CN113896256A
Positive electrode lithium supplement agent and preparation method thereof
CN115064698A
Positive electrode lithium supplement agent and preparation method and application thereof
CN118554039A
Manufacture of linio2 for lithium secondary battery
JP1997259881A
Cited By
Nickel hydroxide precursor for preparing nickel protoxide as well as preparation method and application of nickel hydroxide precursor
CN122627478A